PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019. - Tilam Sari, Titis; Yulianti, Nita; Adhani, Ida (Accounting Research and Business Journal, 2023)
ABSTRACT This study aims to determine the effect of Good Corporate Governance and Company Size on Financial Performance. The sample of this research is 34 property and real estate companies listed on the Indonesia Stock Exchange (IDX) with a total of 170 data for the 2015-2019 period. Sampling method using analysis, coefficient of determination, t test, f test, and multiple linear regression analysis. The results of the study show that of the six independent variables analyzed, the Board of Directors (DD), Managerial Ownership (KM), and Company Size have no significant effect on Financial Performance. While the variables of the Board of Commissioners (DK) and the Audit Committee (KA) have a significant influence on financial performance. The coefficient of determination shown from the adjusted R2 value is 0.582. This means that 58.2% of the dependent variable, namely Financial Performance, can be explained by five independent variables, namely the Board of Directors (DD), Board of Commissioners (DK), Audit Committee (KA), Managerial Ownership (KM), and Company Size (UP). , while the remaining 41.8% is explained by other variables outside the research model.